Proceedings of the 21st International Academic Mindtrek Conference 2017
DOI: 10.1145/3131085.3131117
|View full text |Cite
|
Sign up to set email alerts
|

The role of social media in artisanal production

Abstract: We present craft beer as part of an artisan industry case study that demonstrates how the use of social media creates a community narrative that engages both producer and consumer around the artisanal produce and its values. In contrast to mass drinks production, the past decade has seen a resurgence in specialist artisan 'craft beer' producers, making niche, high-quality products. Speciically, we examine the craft beer industry's use of digital technologies as a way of engendering bilateral consumer engagemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Some key reasons were identified for using social media such as low cost, quick recognition, worldwide distribution area and direct consumer engagement for more personal communication with customers (Rianto Rahadi and Andretti Abdillah, 2013). Another case study of craft beer in the UK demonstrated the role of social media to strengthen the relationship between small artisan industries and their consumers (Foster et al, 2017).…”
Section: Social Media Marketing In the Handicraft Industrymentioning
confidence: 99%
“…Some key reasons were identified for using social media such as low cost, quick recognition, worldwide distribution area and direct consumer engagement for more personal communication with customers (Rianto Rahadi and Andretti Abdillah, 2013). Another case study of craft beer in the UK demonstrated the role of social media to strengthen the relationship between small artisan industries and their consumers (Foster et al, 2017).…”
Section: Social Media Marketing In the Handicraft Industrymentioning
confidence: 99%
“…Social media and current trends contributed the most to this change". Interesting research [73] showcases how the utilization of social media cultivates a communal storyline that involves both producers and consumers in the realm of artisanal products and their principles. Recognized as vital participants within the craft beer community, stakeholders encompass craft brewers, retailers, bloggers, and enthusiasts.…”
Section: Social Media and Marketingmentioning
confidence: 99%
“…A growing body of HCI work has examined the digital innovation within traditional handicraft, both within Western [11,13,37,54] and developing contexts [53,64]. Such work has explored digital technologies for accessing and storing tangible and intangible cultural heritage [13], particularly in interactive museums [37] to support richer user engagement.…”
Section: Crafts and Practices In Hcimentioning
confidence: 99%